Efficiency Improvement of Solution‐Processed Dithienopyrrole‐Based A‐D‐A Oligothiophene Bulk‐Heterojunction Solar Cells by Solvent Vapor Annealing. Issue 14 (30th May 2014) - Wessendorf, Cordula D.; Schulz, Gisela L.; Mishra, Amaresh; Kar, Prasenjit; Ata, Ibrahim; Weidelener, Martin; Urdanpilleta, Marta; Hanisch, Jonas; Mena‐Osteritz, Elena; Lindén, Mika; Ahlswede, Erik; Bäuerle, Peter
<x xml:space="preserve">Abstract</x> The extension of a series of dithienopyrrole containing A‐D‐A oligothiophenes for application in solution‐processed bulk heterojunction solar cells is described. Using solvent vapor annealing, power conversion efficiencies up to 6.1% are obtained. Exposure of the photoactive layer to chloroform vapor results in increased absorption and ordering of the donor:acceptor blend, as is evident from UV‐vis absorption spectroscopy, X‐ray diffraction (XRD) spectroscopy, and atomic force microscopy (AFM). The type and position of the solubilizing alkyl chains influences the dissolution, optical, and packing properties of the oligomers. However, despite subtle differences in molecular structure, all electron donors could be implemented in solar cells demonstrating power conversion efficiencies between 4.4 and 6.1%. Upon further optimization of these in‐air, processed devices, it is expected that additional improvements in photovoltaic performance can be achieved.